Biophilic design, neuroarchitecture and therapeutic home environments: harnessing medicinal properties of intentionally-designed spaces to enhance digital health outcomes - Bulaj, Grzegorz; Forero, Maria; Huntsman, Dorothy Day (Frontiers in Medicine, 2025)
Digital health technologies (DHT) support patient-centered care by delivering behavioral, educational, self-efficacy and self-management interventions. Yet, multifactorial chronic diseases are shaped by complex interactions between genetics, environment and behavior, embodied in social and commercial determinants of health. Given that people in the United States spend on average 18 h per day at home, the impact of home environment on a person's health is underutilized in medicine. Herein, we discuss opportunities to improve therapy outcomes through bridging digital interventions with intentionally-designed restorative and multisensory environments that simultaneously foster physiological and emotional homeostasis. Harnessing positive effects of biophilic design, neuroarchitecture and therapeutic home environments can enhance the effectiveness of digital interventions, including digital therapeutics (DTx), wearables and drug + digital combination therapies that utilize “prescription drug use-related software” (PDURS) framework. Real-world barriers to advance these solutions include a lack of public awareness about connections between the built environment, health and wellbeing, the knowledge gap in long-term clinical outcomes of biophilic interventions, and a limited funding for advancing “biophilic design as an adjunctive therapy” applications. In conclusion, creating digital health ecosystems that favor symbiosis between digital health interventions and enriched environments can promote sustained behavior change, elevate precision care and improve value-based healthcare outcomes.